2012
DOI: 10.1109/tit.2012.2193374
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Constellations for Single-Subcarrier Intensity-Modulated Optical Systems

Abstract: We optimize modulation formats for the additive white Gaussian noise channel with nonnegative input, also known as the intensity-modulated direct-detection channel, with and without confining them to a lattice structure. Our optimization criteria are the average electrical, average optical, and peak power. The nonnegative constraint on the input to the channel is translated into a conical constraint in signal space, and modulation formats are designed by sphere packing inside this cone. Some dense packings are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 56 publications
(121 reference statements)
2
39
0
Order By: Relevance
“…Next, we study the behavior of the optimal solution at high, low, and moderate SNR. 5 We formally define c N +1 = 0. 6 For brevity, occasionally we will use '+' and '−' to denote E This article has been accepted for publication in a future issue of this journal, but has not been fully edited.…”
Section: B Intensity Allocation Given Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we study the behavior of the optimal solution at high, low, and moderate SNR. 5 We formally define c N +1 = 0. 6 For brevity, occasionally we will use '+' and '−' to denote E This article has been accepted for publication in a future issue of this journal, but has not been fully edited.…”
Section: B Intensity Allocation Given Hmentioning
confidence: 99%
“…Of particular interest are systems employing intensitymodulation and direct-detection (IM-DD) due to their practical simplicity. For instance, [5], [6] studied constellation design and [7]- [9] studied OFDM for IM-DD systems. Informationtheoretic achievable rates in IM-DD channels have been studied in [10] which focused on on-off keying, and in [11] which considered higher order modulation.…”
Section: Introductionmentioning
confidence: 99%
“…To prove its asymptotic tightness at low SNR, we inspire from earlier works asserting the optimality of binary inputs at low SNR, such as [4], [32], [33]. We show that the asymptotically low-SNR optimal input in the MIMO IM-DD context is a maximally correlated vector-binary distributed input.…”
Section: Introductionmentioning
confidence: 99%
“…The optimization of a set of M -ary (e.g. M = 4, 8, 16) single-subcarrier modulation formats for IM/DD systems with and without confining them to a lattice structure was studied in [29] and a wider class of pulse sets were considered. The gain of the optimized formats over previously known formats range from 0.3 dB to 1 dB.…”
Section: Previous Workmentioning
confidence: 99%
“…The gain of the optimized formats over previously known formats range from 0.3 dB to 1 dB. A simplified two-dimensional signal space with reduced complexity compared to the three-dimensional formats studied in [29] was presented in [30]. It was shown that the two-dimensional formats wee good for single-wavelength optical systems since the formats have superior performance if the bandwidth is measured as 90% in-band power.…”
Section: Previous Workmentioning
confidence: 99%